Distribution patterns of deep-sea benthopelagic fish off Algarve coast, Portugal - Alagador, Diogo (2020)
The present study characterises and compares the structure and diversity of the deep-sea benthopelagic ichthyofauna off the southern Portuguese coast, according to the biomass values –in kg/(nautical mile)2– of ten teleost and seven chondrichthyan species. The differences between the biomass of benthopelagic species were assessed by depth interval and sampling season. It seems clear that even at 100 m depth intervals there are differences within the fish assemblages, and that a few species make most of the contribution to such differences. No traces of seasonality or even differences between the sampling years have been found. There is a separation between slope habitats